Towards autonomous robotic systems 12th annual conference, TAROS 2011, Sheffield, UK, August 31 - September 2, 2011. Proceedings - Groß, Roderich; Alboul, Lyuba; Melhuish, Chris; Witkowski, Mark; Prescott, Tony J; Penders, Jacques; SpringerLink (Online service). (Berlin, Heidelberg Springer Berlin Heidelberg, 2011)
This book constitutes the refereed proceedings of the 12th Annual Conference Towards Autonomous Robotics Systems, TAROS 2011, held in Sheffield, UK, in August/September 2011. The 32 revised full papers presented together with 29 two-page abstracts were carefully reviewed and selected from 94 submissions. Among the topics addressed are robot navigation, robot learning, human-robot interaction, robot control, mobile robots, reinforcement learning, robot vehicles, swarm robotic systems, etc.
Electronic reproduction.
Keywords: Electronic books; Computer science; Artificial intelligence; Computer vision; Image processing equipment industry; User Interfaces (Computer systems).